THE ROLE OF DIRECTORATE GENERAL OF CUSTOMS AND EXCISE IN HANDLING COVID-19 PANDEMIC AS A TRADE FACILITATOR AND INDUSTRIAL ASSISTANCE IN INDONESIA - Ahmad Romadhon (Transpublika Publisher, 2022)
This paper seeks to examine the role of Directorate General of Customs and Excise as an institution under The Ministry of Finance of Indonesian Republic in its function as a trade facilitator and industrial assistance in handling Corona Viruses Disease 2019 (Covid-19) pandemic in Indonesia. As covid-19 has been made crisis in almost every country around the world, it is being concerned about the shortage of health supplies that needed to prevent the deployment of the viruses and for the treatment process. Besides that, company continuity during pandemic was also threatened due to the decrease of demand and activities. Having function in international trade and industrial assistance, Directorate General of Customs and Excise are capable in helping central government by using its function as a trade facilitator and industrial assistance with (two) major key, first is helping maintain the availability of the health supplies that needed in handling covid-19 pandemic, and the second is providing additional incentives for companies of bonded zone facilities and/or companies that receive ease of import for export purpose facility.